Improvement of pregnancy rate after deep uterine artificial insemination with frozen-thawed cauda epididymal spermatozoa in Hanwoo cattle - Sung-Sik Kang; Ui-Hyung Kim; Jun Sang Ahn; Jeong Il Won; Sang-Rae Cho (The Korean Society of Animal Reproduction and Biotechnology, 2021)
In the present study, we examined if deep uterine artificial insemination (DUAI) can improve the pregnancy rate of artificial insemination (AI) using epididymal spermatozoa (ES) in Hanwoo cattle. The estrus cycles of 88 Hanwoo cows were synchronized, and 17 cows were artificially inseminated using the DUAI method with ES, 20 cows were artificially inseminated via the uterine body (BUAI) method with ES, and as a control, 51 cows were inseminated by using the BUAI method with ejaculated spermatozoa from 1 proven bull after frozen thawing. The pregnancy rate of the DUAI method (58.8%) was higher than that of the BUAI method (25.0%, p = 0.0498). The motility of ES was examined immediately after thawing and after 3 and 6 h of incubation. The rapid progressive sperm motility of the control group was significantly higher than that of the ES group immediately after thawing and after 3 and 6 h of incubation (p < 0.05). The straight line velocity and average path velocity of the ES group after 6 h of incubation were significantly lower than those in the control group (p < 0.05). The linearity and amplitude of lateral head of ES were lower than those at 6 h (p < 0.05). The flagellar beat cross frequency and hyperactivation of ES were lower than the control spermatozoa immediately after thawing and at 3 h (p < 0.05). These motility parameters suggested that ES had a low motility and fertilization ability compared to the control spermatozoa. After frozen-thawing and 3 h of incubation, the percentage of live spermatozoa with intact acrosomes in the ES was significantly lower than that in ejaculated spermatozoa (p < 0.05). Our findings suggested that the DUAI method can overcome the low pregnancy rate of ES, despite the low motility, viability, and fertilization ability of ES.